The Way of the cross suffering selfhoods in the Roman Catholic Philippines - Bautista, Julius (Honolulu University of Hawaiʻi Press, 2019)
"Every year during Holy Week in the Philippine province of Pampanga, hundreds of men and women undergo acts of excruciating, self-inflicted pain in ways that evoke the Way of the Cross: the torment and crucifixion that Christ endured in the last days of his earthly existence. Because these Passion rituals are officially disavowed by the Filipino Roman Catholic Church, most observers view them as irrational and extremist mimicry of Christ's painful ordeal. Even scholars conventionally depict them as theatrical "spectacle" or macabre examples of Filipino "folk religion." But what conditions enable ritual actors to submit to such extreme pain? What justifications do they give for going against official prohibitions? What outcomes do they seek in channeling Christian piety in this way? This book addresses these questions through its in-depth analyses of three interconnected ritual acts: the pabasa, a days-long communal chanting of Christ's Passion story; the pagdarame, the public self-flagellation of hundreds of devotees, and the pamamaku king krus, in which steel nails are driven through the palms and feet of ritual practitioners as part of a street play performed in front of tens of thousands of spectators. Bautista suggests that such ritual acts manifest the embodied physicality of a suffering selfhood that facilitates the expression of heartfelt sentiments of pity, empathy, trust, and bereavement. The author draws on a decade of in-depth and often exclusive interviews with a host of local stakeholders and his own participation in a Passion play. Ethnographic insight is considered alongside primary and secondary archival sources, including unpublished, locally produced oral historical accounts and a survey of relevant media coverage"--
The ideology of suffering in Medieval and colonial domains -- The ensounded body: the aural environment of passion chanting -- Pagdarame: self-flagellation as triangulated empathy -- The way of the cross: nailing and the ritualization of trust -- Clerical perspectives on passion rituals -- Suffering selfhood in transnational domains.
Includes bibliographical references and index.
Keywords: Catholic Church -- Philippines -- Pampanga -- Customs and practices; Scourging of Christ, Devotion to -- Philippines -- Pampanga; Flagellation -- Philippines -- Pampanga; Pampanga (Philippines) -- Religious life and customs